Stimulation of gross chromosomal rearrangements by the human CEB1 and CEB25 minisatellites in Saccharomyces cerevisiae depends on G-quadruplexes or Cdc13. - Aurèle Piazza; Alexandre Serero; Jean-Baptiste Boulé; Patricia Legoix-Né; Judith Lopes; Alain Nicolas (PLoS Genetics)
Genomes contain tandem repeats that are at risk of internal rearrangements and a threat to genome integrity. Here, we investigated the behavior of the human subtelomeric minisatellites HRAS1, CEB1, and CEB25 in Saccharomyces cerevisiae. In mitotically growing wild-type cells, these GC-rich tandem arrays stimulate the rate of gross chromosomal rearrangements (GCR) by 20, 1,620, and 276,000-fold, respectively. In the absence of the Pif1 helicase, known to inhibit GCR by telomere addition and to unwind G-quadruplexes, the GCR rate is further increased in the presence of CEB1, by 385-fold compared to the pif1Δ control strain. The behavior of CEB1 is strongly dependent on its capacity to form G-quadruplexes, since the treatment of WT cells with the Phen-DC(3) G-quadruplex ligand has a 52-fold stimulating effect while the mutation of the G-quadruplex-forming motif reduced the GCR rate 30-fold in WT and 100-fold in pif1Δ cells. The GCR events are telomere additions within CEB1. Differently, the extreme stimulation of CEB25 GCR depends on its affinity for Cdc13, which binds the TG-rich ssDNA telomere overhang. This property confers a biased orientation-dependent behavior to CEB25, while CEB1 and HRAS1 increase GCR similarly in either orientation. Furthermore, we analyzed the minisatellites' distribution in the human genome and discuss their potential role to trigger subtelomeric rearrangements.